(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article explores the current trends and enabling technologies in the field of adaptive control for robotic systems. It discusses the shift toward intelligent, learning-based approaches, the integration of artificial intelligence, and the emergence of hybrid control architectures. Key technologies that support reliable robot behavior in uncertain and dynamic environments are presented. The paper also outlines future prospects and challenges for research and implementation.